Risk analysis of tobacco farming in Bajang Village, Pakong Sub-District, Pamekasan District - Yuliana, Ratih; Zuhriyah, Amanatuz (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2024)
In fact, the magnitude of the economic potential worth of tobacco commodities is not directly proportionate to the conditions encountered by farmers in the field. Tobacco farmers in Bajang Village are faced with many problems that may indicate risks that threaten the sustainability of farming activities. The goals of this research are to: (1) identify the risks faced by farmers in tobacco farming, (2) evaluate the level of risk in tobacco farming, and (3) examine the composition of mitigation strategy for prioritized risks in tobacco farming in Bajang Village. Respondents in this study consisted of key informants and 43 farmers using the Fishbone Diagram and FMEA (Failure Mode and Effect Analysis) analysis methods. According to the analysis result, there are a total of 15 risks based on five risk sources: production, price and market, finance, human resource, and institutional. Weather and climate uncertainty, price uncertainty, quality and quantity uncertainty, pest and disease attacks, and farmers' lack of insight are the top five risks. Mitigation strategies are presented in an attempt to lessen the impact of risks on tobacco farming.